Microstructure characterization and mechanical properties of Ti-based bulk metallic glass joints prepared with friction stir spot welding process. (15th June 2016) - Jamili-Shirvan, Zahra; Haddad-Sabzevar, Mohsen; Vahdati-Khaki, Jalil; Chen, Na; Shi, Qingyu; Yao, Ke-Fu
Abstract: In this study, TiZrFeBeCu bulk metallic glass plates have been welded together by using the friction stir spot welding method. The effects of processing parameters on the microstructure and mechanical properties of the joints have been studied. It has been found that the plunge depth has a crucial effect on the fracture mode and fracture strength of the joint. Both tool rotation speed and holding time significantly influence the tensile/shear fracture load and the fracture toughness. The correlation between fracture surface and the fracture toughness have been analyzed. The results revealed that there exist three regions in the spot welding of bulk metallic glass plates: stirring zone, thermo mechanically affected zone and base metal. It shows that stirring zone under the tool shoulder and around the tool tip possesses different structures and micro-hardness from that beneath the tool tip. The thermo mechanically affected zone and the stirring zone under the tool tip have similar hardness and structure. Stress relief annealing was used to clarify the reason for the hardness difference at different regions. Changes in the hardness in different areas of the welding spot can be correlated with the shear bands pattern and plastic zone size around the Vickers indents. Graphical abstract: Highlights: Joining of a Ti-based strong glass former using friction stir spot welding process was studied. Effects of welding parameters on the fracture load and fractured surfaces were analyzed. Different zones in the weld spot were characterized and stir zone, TMAZ and base metal were identified. Nano crystal/BMG's composite formation in the stir zone under the tool shoulder was the reason for higher fracture load. Stir zone under the tool tip and the TMAZ had similar hardness and shear bands pattern with different structural reasons.